Antimicrobial Resistance Profile of mcr-1 Positive Clinical Isolates of Escherichia coli in China From 2013 to 2016 - Li, Baiyuan; Ke, Bixia; Zhao, Xuanyu; Guo, Yunxue; Wang, Weiquan; Wang, Xiaoxue; Zhu, Honghui (Frontiers in Microbiology, 2018)
Multidrug-resistant (MDR) Escherichia coli poses a great challenge for public health in recent decades. Polymyxins have been reconsidered as a valuable therapeutic option for the treatment of infections caused by MDR E. coli. A plasmid-encoded colistin resistance gene mcr-1 encoding phosphoethanolamine transferase has been recently described in Enterobacteriaceae. In this study, a total of 123 E. coli clinical isolates in China were tested for susceptibility to 12 antimicrobial agents including polymyxin B. The frequency of resistance to at least three antimicrobial agents was 61.0%, and these isolates were most frequently resistance to ampicillin (67.5%), sulfamethoxazole-trimethoprim (53.7%) and tetracycline (64.2%). Nine isolates (7.3%) were resistant to polymyxin B and they were all MDR. Among them, seven isolated carried at least one copy of the mcr-1 gene by PCR screening. A hybrid sequencing analysis using single-molecule, real-time (SMRT) sequencing and Illumina sequencing was performed next to resolve the genomes of these seven MDR isolates carrying mcr-1. These isolates all harbored multiple plasmids and phenotypic resistance is closely associated with the presence of resistance genes carried on plasmids. Interestingly, the mcr-1 gene was the solo antibiotic resistance gene identified in these plasmids. The rest of the resistance genes were mostly clustered into one or two plasmids. In addition, analysis of the sequenced mcr-1 carrying plasmids in the NCBI database suggests that the possible fusions of mcr-1 positive plasmids and plasmids carrying other resistance genes can occur and this would promote the co-transfer of mcr-1 and other antimicrobial resistance genes by hybrid plasmids. This emphasizes the need for ongoing monitoring of resistance patterns in clinical isolates to ensure appropriate antibiotic use by the clinicians.